2021
DOI: 10.1523/jneurosci.1478-20.2021
|View full text |Cite|
|
Sign up to set email alerts
|

REST Protects Dopaminergic Neurons from Mitochondrial and α-Synuclein Oligomer Pathology in an Alpha Synuclein Overexpressing BAC-Transgenic Mouse Model

Abstract: Alpha-synuclein pathology is associated with dopaminergic neuronal loss in the substantia nigra (SN) of Parkinson's patients. Working across human and mouse models, we investigated mechanisms by which the accumulation of soluble a-synuclein oligomers leads to neurodegeneration. Biochemical analysis of the midbrain of a-synuclein overexpressing BAC-transgenic male and female mice revealed age-and region-dependent mitochondrial dysfunction and accumulation of damaged proteins downstream of the RE1 Silencing Tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 59 publications
2
11
0
Order By: Relevance
“…In agreement with recent results obtained in dopaminergic neurons (Ryan et al, 2021 ), we show that REST deficiency contributes to cellular dysfunction by blocking autophagic protein clearance. We provide data for this blockade at both structural and functional levels.…”
Section: Discussionsupporting
confidence: 94%
“…In agreement with recent results obtained in dopaminergic neurons (Ryan et al, 2021 ), we show that REST deficiency contributes to cellular dysfunction by blocking autophagic protein clearance. We provide data for this blockade at both structural and functional levels.…”
Section: Discussionsupporting
confidence: 94%
“…Growing evidence shows that REST is neuroprotective, and its dysfunction may contribute to the neuropathology of multiple neurological disorders, such as PD, dementia with Lewy body ( 39 , 53 ), and AD ( 38 ). Decreased REST levels were correlated with higher oxidative stress and apoptotic events with dementia in AD brains compared with normal healthy brains ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence has shown that REST exerts neuroprotective effects against several neurodegenerative diseases, including AD ( 38 ), PD ( 39 ) and experimental 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)–induced PD models ( 52 ). Reduced REST levels exacerbated mitochondrial dysfunction and correlated with α-synuclein accumulation in an α-synuclein-overexpressed PD mouse model ( 53 ). Mn decreased REST expression in dopaminergic neuronal cells, leading to a decrease in tyrosine hydroxylase expression, resulting in neuronal toxicity ( 50 ).…”
mentioning
confidence: 99%
“…Indeed, recent data showed that CRISPR-mediated REST KO induced mitochondrial dysfunction and impaired mitophagy in vitro. Furthermore, REST overexpression impedes mitochondrial toxicity and mitochondrial morphology disruption through the transcription factor PGC-1α [41].…”
Section: Discussionmentioning
confidence: 99%